The violent dissident republican threat - Silke, Andrew (Pool Reinsurance (PoolRe), 2019)
Though often overlooked in recent years, terrorism related to Northern Ireland is still a possible threat to the UK. Since the signing of the Good Friday Peace Agreement in 1998, over 150 people have been killed as a result of security-related violence in the region. 1 A young journalist, Lyra McKee, became the latest fatality when she was shot and killed by violent dissident republicans (VDRs) during a riot in Derry in April. On average between 15-40 shootings and bombings take place each year though media coverage of the incidents outside of Northern Ireland is very limited and wider awareness of the violence is low. In the 12 months up to March 2019, the Police Service of Northern Ireland (PSNI) recorded 15 bombings and 38 security-related shootings in the province. 2 While there is no denying that the level of violence has declined massively compared to that seen before the Good Friday Agreement, it is still vital to realise that a variety of terrorist organisations remain active.
Keywords: Violent Dissident Republican terrorism; Northern Ireland; IRA